2020
DOI: 10.1620/tjem.251.117
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mannose-Binding Lectin Levels Are Correlated with the Disease Activity of Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A Single-Center Study

Abstract: Mannose-binding lectin (MBL) is a soluble pattern-recognition molecule, which plays a crucial role in the innate immune system and the activation of lectin complement pathway. Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an autoimmune disease affecting the small vasculatures and is characterized by the alteration of innate and adaptive immunity and complement activation. In this study, we investigated whether serum MBL is associated with disease activity of AAV, which was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…MPA was the most frequent in AAV [19,20] . In the current study, 79.3% of AAV was diagnosed with MPA.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…MPA was the most frequent in AAV [19,20] . In the current study, 79.3% of AAV was diagnosed with MPA.…”
Section: Discussionsupporting
confidence: 47%
“…MPA was the most frequent in AAV. [ 19 , 20 ] In the current study, 79.3% of AAV was diagnosed with MPA. Previous studies have indicated that the positivity rate of ANA was higher in females than that in males.…”
Section: Discussionmentioning
confidence: 50%
“…There have been several reports about the association between PRMs and disease activity of autoimmune diseases. High serum MBL level was reported to be associated with thrombocytopenia and seizure in patients with SLE [22], and serum MBL was reported to be positively correlated with Birmingham Vasculitis Activity Score in patients with antineutrophil cytoplasmic antibody-associated vasculitis [23]. In addition, serum ficolin-1 was positively correlated with disease activity in patients with rheumatoid arthritis (RA) [24] and juvenile idiopathic arthritis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excessively high activity of the lectin pathway may be a risk factor for the predisposition and more severe course of certain diseases: infections caused by intracellular bacteria and parasites including leprosy, 43,45,46 tuberculosis, 31,47 leishmaniasis, 48,49 schistosomiasis, 50 pneumonia caused by Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella pneumophila, Coxiella burnetii, 51 a hyperinflammatory syndrome in some infections, including SARS-CoV-2, [52][53][54] atherosclerosis and associated cardiovascular diseases, 26,[55][56][57] diabetes, [58][59][60][61] some forms of autoimmune diseases, in particular, through the regulation of transcription factors. [62][63][64] Currently, very successful attempts are being made to inhibit the lectin pathway of complement activation using monoclonal antibodies against MASP-2 (Narsoplimab, OMS721) in atypical haemolytic uremic syndrome (Clini calTr ials.gov Identifier: NCT03205995), IgA nephropathy, 65 thrombotic microangiopathy after stem cells transplantation, 66 as well as SARS-CoV-2. 67,68 A detailed review of the therapeutic possibilities of complement modulation is given in a recent review by Garred, Tenner, and Mollnes.…”
Section: Discussionmentioning
confidence: 99%